Alternative long-ranged charge optimized many-body potential for aluminium. (13th November 2017) - Mo, Yunjie; He, Yingyou; Feng, Xiaofang; Jiang, Shaoji
Abstract: A new COMB3 potential was developed for aluminium, which focuses on long-range interaction and phase transition. The potential was developed by fitting the equilibrium lattice properties of different phases and defects to ensure its transferability to general systems. The quality of the potential was tested in several problems and compared with the EAM potential as well as the published COMB3 potential, the effect of the cutoff method was studied in detail to demonstrate the necessity to extend the cutoff region. Systems of strong deformations along the Bain path, under a trigonal strain and with planar stacking faults were calculated and the present potential performed as well as the EAM potential. At last, a surface process that involves adsorption and diffusion was studied using the present potential.